(untitled) (Global Journal of Management and Business Research, 2014)
The study was carried-out to assess the contribution of internally generated revenue before (TIN) on total tax revenue in Kogi State. The related literatures were reviewed. The population of study comprises the Total Tax Revenue Before TIN (TRBT) and Internally Generated Revenue Before TIN (IGRBT). A number of statistical tools including tables and Regression were used to analysed the data and test the hypothesis formulated. Our analysis of data revealed that, the internally generated revenue (IGR) before the introduction of TIN within (2003TIN within ( -2007) ) was not significant. We recommended that a holistic tax education should be carried out in order to keep the teeming taxpayers abreast of the need to pay their taxes to the state and the enforcement unit of the State Revenue Board should be properly empowered to monitor, enforce and prosecute any errant tax defaulters who fail to comply with tax authority.